THE NEGATIVE INFLUUENCE FROM INDONESIAN TO ENGLISH: A CASE IN THE ARTICLE “ABOUT BALI” - Kade Dwijati, Ida Ayu (Lingual Journal of Language and Culture, 2016)
This study focuses on finding out the aspects of language being interfered and the factors which caused those interferences in the English article ‘About Bali’ published on the official website of Bali Government Tourism Office. It is found that the interferences in terms of semantics in which the writer/translator’s word choices were interfered by the lexical meaning without considering the grammatical context of the sentence where those particular words are places. Besides, the copula ‘are’ was missing in one of the sentences which caused the meaning of the sentence become incomplete. The uses of singular and plural markers are not consistent. These interferences are caused by the influence of Indonesian language mastered by the writer/translator that showed the lack of knowledge regarding the rules of both English and Indonesian languages, meaning of words that were chosen, the direct translation from Indonesian into English which affected the structure, word choices and the meaning in the target language.
Keywords: interference, language aspect, factors